Reciprocidade nas trocas sociais de crianças e adolescentes: um estudo sobre aspectos cognitivos, sociais, afetivos e morais do desenvolvimento. - Bastos, Caroline Benezath Rodrigues (2020)
The objective of this research was to investigate how reciprocity occurs in the social exchanges of children and adolescents. Cognitive, social and moral aspects of human development were evaluated in the context of how these aspects are related to the ma